DEVELOPMENT OF INNOVATIVE ACTIVITY OF SMALL ENTERPRISES BASED ON TECHNOLOGY TRANSFER - GONTAREVA, IRYNA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The economic development of any country is closely linked with the development of small business. Entrepreneurship is especially important for countries whose economies are in the process of structural change. The essence of small business development reflects the constant search for new opportunities, independence in making innovative decisions, perseverance and determination in their promotion in foreign and domestic markets. Given the scale of activities and narrow specialization, technology transfer is the basis of innovative activities of small businesses and a means of their sustainable development, a guarantee of profit and social impact. The purpose of the article is to identify information and communication tools for technology transfer for the development of innovative activities of small businesses.Accelerating the development of information and communication technologies, their penetration into all spheres of society, has made significant changes in the conditions of origin and implementation of entrepreneurial activity. There are new forms of relations between producers and consumers, managers and staff, between business partners. Information and communication technologies means a systemically connected set of methods and means of intellectual work associated with the search, accumulation, processing and protection of information, as well as its exchange between participants in joint activities. Practice shows that small enterprises carry out ICT transfer and use them in their activities (commercialize), receive additional opportunities. To achieve optimal results, technology transfer, like any other business activity, requires attention, flexible approaches and integration into the overall strategy of innovative development.The direction of further research is an empirical study of the results of technology transfer by local enterprises.
Keywords: technology transfer; small enterprises; innovation; development; information and communication technologies